2015
DOI: 10.1080/08985626.2014.995722
|View full text |Cite|
|
Sign up to set email alerts
|

Be creative but not so much. Decreasing benefits of creativity in clustered firms

Abstract: Registro de acceso restringido Este recurso no está disponible en acceso abierto por política de la editorial. No obstante, se puede acceder al texto completo desde la Universitat Jaume I o si el usuario cuenta con suscripción. Registre d'accés restringit Aquest recurs no està disponible en accés obert per política de l'editorial. No obstant això, es pot accedir al text complet des de la Universitat Jaume I o si l'usuari compta amb subscripció. Restricted access item This item isn't open access because of publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 143 publications
(193 reference statements)
2
8
1
2
Order By: Relevance
“…Aligned with those recent studies, our results suggest that closed networks provide firms with both advantages (e.g., information exchange, access to valuable assets, low opportunistic behavior, cooperative environment, low agency and transaction costs, and improved adaptability to change) and disadvantages (e.g., redundant information, inertia, myopia, and costs of maintaining connections) in regard to generating innovations. More specifically, we provided empirical evidence for the inverted-U shape between closed networks and innovation in the tourism context, which has been previously proposed in industrial clusters studies (Belso-Martínez & Molina-Morales, 2013; del Corte-Lora et al, 2015; Lechner et al, 2010; Molina-Morales & Martínez-Fernández, 2009b). Second, this study adds to the existing model by introducing the positive moderating effect of diverse networks.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…Aligned with those recent studies, our results suggest that closed networks provide firms with both advantages (e.g., information exchange, access to valuable assets, low opportunistic behavior, cooperative environment, low agency and transaction costs, and improved adaptability to change) and disadvantages (e.g., redundant information, inertia, myopia, and costs of maintaining connections) in regard to generating innovations. More specifically, we provided empirical evidence for the inverted-U shape between closed networks and innovation in the tourism context, which has been previously proposed in industrial clusters studies (Belso-Martínez & Molina-Morales, 2013; del Corte-Lora et al, 2015; Lechner et al, 2010; Molina-Morales & Martínez-Fernández, 2009b). Second, this study adds to the existing model by introducing the positive moderating effect of diverse networks.…”
Section: Discussionsupporting
confidence: 59%
“…We demonstrated that the benefits of this type of network structure on firm innovation become negative beyond a certain point, as hypothesized. In this sense, our study contributes to both the traditional social capital literature that proposes a direct and positive link between dense and strong-tie networks and innovation (del Corte-Lora et al, 2015; Molina-Morales & Martínez-Fernández, 2010; Obstfeld, 2005; Tsai & Ghoshal, 1998, among others), and the more recent body of literature that has started questioning the directionality of that relationship (Expósito-Langa & Molina-Morales, 2010; Guler & Nerkar, 2012; Molina-Morales et al, 2011; Parra-Requena et al, 2015, among others). Aligned with those recent studies, our results suggest that closed networks provide firms with both advantages (e.g., information exchange, access to valuable assets, low opportunistic behavior, cooperative environment, low agency and transaction costs, and improved adaptability to change) and disadvantages (e.g., redundant information, inertia, myopia, and costs of maintaining connections) in regard to generating innovations.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…The data also indicated that lower levels of 'evaluation and judgment' were perceived in entrepreneurs with high EX and high openness than in entrepreneurs with low EX and high openness. The trait of openness has been a strong predictor of human creativity, which may lead to illegal or immoral decisions that harm entrepreneurial innovation and firm performance (Cropley, 2010;Del-Corte-Lora, Vallet-Bellmunt, & Molina-Morales, 2015). Extroverted people enjoy interacting with people and may compromise their judgment when excessive openness to others is involved.…”
Section: Discussionmentioning
confidence: 99%
“…L'étude des clusters et de l'innovation collective s'envisage le plus souvent sous l'angle de l'économie géographique évolutionnaire (Boschma, Frenken, 2011 ;Kogler, 2015) et elle a récemment produit trois résultats majeurs. Le premier concerne le rôle de la variété technologique (Frenken et al, 2007), le second concerne l'analyse de la topologie des réseaux relationnels sous-jacent à ces clusters et à leur cycle de vie et enfin ces réseaux sont des marqueurs de la résilience des territoires (Boshma, 2015 ;Crespo et al, 2014 ;Martin, 2012) et du potentiel innovant des organisations concernées (Cattani, Ferriani, 2008 ;Ahuja 2000 ;Del-Corte-Lora et al, 2015). Au delà de l'engouement, tant du coté des pouvoirs publics que des chercheurs, autour de l'objet cluster Martin, Sunley, 2003), celui-ci s'impose parce que les produits ou les technologies qu'ils sont censés produire sont devenus complexes et composites.…”
Section: Introductionunclassified